Параметрический синтез робастной системы управления магнитным полем технических объектов - Розов, Владимир Юрьевич; Кузнецов, Борис Иванович; Ассуиров, Дмитрий Александрович; Давыдов, Алексей Александрович (НТУ "ХПИ", 2010)
The mathematical model of the magnetic field of technical objects as plant of robust control system synthesis of parameters is developed. The example of dynamic characteristics for such system is given.
Synthesis of parameters for technical objects magnetic field robust control system
Keywords: модель математическая; ПИД регулятор; магнитостатика; программирование квадратичное